1D Hybrid Tin Oxide Nanostructures: Synthesis and Applications - Suman, Pedro H. [UNESP]; Jorgetto, Alexandre O. [UNESP]; Romeiro, Fernanda C. [UNESP]; Felix, Anderson A. [UNESP]; Morais, Paulo V. [UNESP]; Melquíades, Miécio O. [UNESP]; Orlandi, Marcelo O. [UNESP] (Wiley, 2022)
Tin oxide is one of the most relevant semiconducting metal oxides (SMOx) of modern industry. The particular properties of different tin oxide stoichiometries (SnO2, Sn2O3, Sn3O4, and SnO) make them exciting materials for a wide variety of technological applications. One-dimensional (1D) nanomaterials, including nanowires, nanotubes, nanobelts, and nanofibers, are fascinating structures for a new generation of sensing and optoelectronic devices, allowing miniaturization, system integration, and low power consumption. This chapter introduces state-of-the-art research on the synthesis and applications of pristine and hybrid 1D tin oxide nanostructures. Easy controlling methods used to produce such materials and their recent application in gas sensing, photocatalysis, and other relevant purposes will be reviewed. Lastly, future outlooks concerning the application of multiple tin oxide materials will be addressed.
Keywords: gas sensing; heterostructures; one-dimensional (1D) nanostructures; photoelectrocatalysis; Sn3O4; SnO; SnO2; tin oxide